Assessment gaps and biases in knowledge of conservation status of fishes - Miqueleiz, Imanol; Bohm, Monika; Ariño, Arturo Hugo; Miranda, Rafael (Aquatic conservation, 2020)
More than 33,500 fish species inhabit freshwater and marine environments, according to FishBase database records. The International Union for the Conservation of Nature (IUCN) has assessed the conservation status of approximately half of them, the lowest percentage in any vertebrate group. In order to identify what factors may underlie this assessment gap, several traits were examined related to distribution, life‐history, taxonomy, conservation, and the economic relevance of species according to their assessment status. IUCN assessment patterns were explored and separate analyses were included for freshwater and marine species. The results showed that IUCN assessments were biased towards economically developed regions, species with early description dates and species covered by current IUCN specialist groups. Species living in remote areas or habitats were more likely to be unassessed. In particular, South America had low assessment levels. Other traits such as commercial importance did not influence the assessment status of fish species. We therefore encourage assessment in poorly assessed areas and taxonomic subgroups to prompt timely conservation action to prevent species extinctions.